(untitled) (The South East European Journal of Economics and Business, 2020)
Constantly growing health needs, changing demographic situation resulting in often prolonged treatment process, technological progress in the field of highly specialised medical procedures and the associated increase in patient awareness translate into an increase in the operating costs of the healthcare sector. The main aim of the study was the assessment of the relationship between the labour costs of medical staff and in-patient curative care costs financed by the main payer over the next decade. The research results confirmed that the assumed increase of expenditures on healthcare sector to the level of 9% of GDP in 2027 (proposed by management units) is unlikely to happen. The research findings were obtained by the implementation of scenario analysis supported by the development trend analysis.